Interferon-alpha (IFN-alpha) production by human intestinal mononuclear cells. Response to virus in control subjects and in Crohn's disease. Issue 7 (July 1992) - Capobianchi, M R; Fais, S; Mercuri, F; Boirivant, M; Dianzani, F; Pallone, F
Abstract : The virus induced production of interferon alpha by human intestinal lamina propria mononuclear cells was investigated. Intestinal and autologous peripheral cells from control subjects and patients with Crohn's disease were cultured in vitro with and without stimulation with the Newcastle disease virus. Interferon alpha was measured and characterised in the culture supernatants after 12 hours and the kinetics of production was evaluated over the following four days of culture. No detectable interferon alpha was found in cultures of unstimulated intestinal and autologous peripheral mononuclear cells from controls and Crohn's disease whereas interferon alpha was released in all cultures stimulated with the virus. In all 12 hours experiments in both groups, virus stimulated intestinal mononuclear cells yielded significantly less interferon alpha than the autologous peripheral cells. The kinetics experiments showed that control intestinal mononuclear cells appeared to be poorly responsive to virus stimulation showing a release of interferon alpha significantly lower than that of the autologous peripheral cells. The interferon alpha release at day 4 by control cells (either intestinal or peripheral) did not differ from that measured after the first 12 hours. In contrast, the interferon alpha produced by Crohn's disease cells progressively increased during the culture period and the amount of interferon alpha measured at day 4 was significantly higher than that released at 12 hours. These data suggest that normal human intestinal mononuclear cells are down regulated in their capability of producing interferon alpha and that in Crohn's disease their activation for this function is enhanced. These data also suggest that in Crohn's disease intestinal mononuclear cells exhibit a transient hyporesponsiveness to in vitro stimulation possibly related to massive in vivo exposure to interferon alpha inducers.